7h+7k-3(8h-5k)=

Simple and best practice solution for 7h+7k-3(8h-5k)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7h+7k-3(8h-5k)= equation:


Simplifying
7h + 7k + -3(8h + -5k) = 0
7h + 7k + (8h * -3 + -5k * -3) = 0
7h + 7k + (-24h + 15k) = 0

Reorder the terms:
7h + -24h + 7k + 15k = 0

Combine like terms: 7h + -24h = -17h
-17h + 7k + 15k = 0

Combine like terms: 7k + 15k = 22k
-17h + 22k = 0

Solving
-17h + 22k = 0

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-22k' to each side of the equation.
-17h + 22k + -22k = 0 + -22k

Combine like terms: 22k + -22k = 0
-17h + 0 = 0 + -22k
-17h = 0 + -22k
Remove the zero:
-17h = -22k

Divide each side by '-17'.
h = 1.294117647k

Simplifying
h = 1.294117647k

See similar equations:

| (x-20)2=289 | | x*2.5=[x-20]5 | | 3(2x-1)+5=6(1x+1) | | 2d+4+d=16 | | 2a-6+5a=3a+1 | | x(2x+11)+9=0 | | 2x^2-20x-42=0 | | x^2-6x=-22 | | -1(1y+8)+6y=-9+5y+1 | | 3(x-1)=3(x-2)+3 | | 27+2x=5x-3 | | 6+-8x=10+-1x | | 5z-9=21 | | 0.01x=1 | | 5x+12=42+2x | | -16x^2+200x-50=0 | | -3(2x-4)-(5x-1)=6(x+1) | | 5z^3+320=0 | | -1y-22=1y-16 | | 27x^3=1000 | | 9x^2-123x-734=0 | | (2.5)x=(x-20)5 | | 3x^2+4x=-5 | | 2[3-4x]=10-x | | 32z^5-2z=0 | | 5h-3h+11=17 | | 3x^2-2x+112=0 | | 8c-3c-18=7 | | h(t)=2t^2+12t | | 4x^4-16x^2+9=0 | | 25+.05y=10+.10y | | (y/3)=-39 |

Equations solver categories